PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION PERAWAT MELALUI STRES KERJA - Irna Wilis; Guston Sitorus; Edi Siregar (Pasca Sarjana Universitas Satya Negara Indonesia, 2025)
Problems related to human resource management that frequently arise in companies are employee turnover. This study aims to understand and analyze the direct and indirect effects of workload, work environment, and compensation on turnover intention through job stress as an intervening variable among nurses at Karang Tengah Medika Hospital, and to provide recommendations that are useful for hospital management in reducing nurses' turnover intention. The research method used is Structural Equation Modeling (SEM) with Partial Least Squares to analyze data obtained from a questionnaire distributed to sixty five nurses at Karang Tengah Medika Hospital. The results of the study show that workload has a significant positive effect on nurses' turnover intention through job stress as an intervening variable. The work environment does not show a significant effect on turnover intention, both directly and through job stress. Meanwhile, compensation was found to have a significant negative effect on turnover intention directly, but no indirect effect through job stress as an intervening variable. This study supports theories explaining that job factors such as workload and compensation affect turnover intention, but not all factors can explain the relationship through job stress. The practical implications of this study show the importance of managing workload, improving fairer compensation, and arranging a more conducive work environment to reduce nurses' turnover intention in hospitals.